Analisis Potensi Obyek Wisata Di Kecamatan Bone Kabupaten Bone Bolango Berdasarkan Kriteria Penilaian Obyek Daya Tarik Wisata (ODTWA) - Kaino, Sri Ayu; Maryati, Sri; Yusuf, Daud (-, 2025)
This study aims to analyze the potential of natural tourism objects in Bone District, Bone Bolango Regency, based on the criteria of Natural Tourism Object Assessment (ODTWA). The research uses a descriptive approach combining quantitative and qualitative methods. Data were collected through observations, interviews with visitors, local communities, and village government officials, as well as questionnaires developed according to 15 ODTWA criteria. The study focuses on three main tourist attractions: Taludaa Beach, Bidadari Pool, and Ilohuuwa Waterfall. Results indicate that Taludaa Beach has the highest potential with strong natural attraction, adequate supporting facilities, ease of access, and environmental cleanliness. Bidadari Pool shows good comfort and service facilities but requires improvement in accessibility. Ilohuuwa Waterfall, while having unique natural beauty, scores lower particularly in accessibility and basic facilities. The discussion highlights supporting factors such as natural beauty and community hospitality, as well as inhibitors like poor infrastructure and limited amenities. Sustainable tourism development requires enhanced facilities, proper resource management, and active community involvement. This study provides important recommendations for the synergy among government, community, and private sector to optimize tourism potential while ensuring environmental preservation and economic benefits